Kernel weight and source/sink dynamics of temperate maize hybrids for diverse end uses across contrasting environments - Chazarreta, Yésica Daniela; Álvarez Prado, Santiago; Otegui, María Elena (Elsevier, 2025)
Context or problem: Maize (Zea mays L.) production in the temperate region of Argentina has shifted significantly over the last decade, due to the widespread adoption of late sowings aimed primarily at mitigating mid-summer water deficits. This shift has promoted the expansion of the production area, diversified crop end-uses, and introduced marked contrasts in growing conditions along the cycle, all trends that demand research attention to guide breeding efforts and management decisions. Objective or research question: The main goal of this study was to assess the effects of environment (two years × two sowing dates) and crop management (nitrogen fertilization) on grain yield, kernel weight (KW), its physiological determinants, source/sink ratios, and water-soluble carbohydrates in stem (WSCS) in eight field-grown temperate maize hybrids bred for different uses (3 graniferous, 2 dual-purpose, 3 silage). Simulations assessed WSCS remobilization (null, partial, or total) between R2 and R6 for different production systems (18 scenarios) and climate conditions (41 growing seasons). Results: Grain yield and KW exhibited significant environment × nitrogen interactions. Nitrogen fertilization increased grain yield by 19–37 % and KW by 13–17 % in early sowings, whereas responses were limited in late sowings (+3–4 % for KW; negligible for yield). Grain hybrids exhibited the highest grain yield, followed by the dual-purpose and the silage type. Dual-purpose and silage hybrids exhibited the highest (293 mg) and the lowest (268 mg) mean KW across environments, respectively, while graniferous hybrids showed the highest source/sink ratio during the effective kernel-filling period (136 mg kernel−1). WSCS remobilization during kernel filling was higher in late (68 %) than in early sowings (32 %), with no consistent differences among hybrid types. Simulations revealed that total WSCS depletion was most frequent in early sowings with low nitrogen (44–51 % of seasons) and late sowings with full nitrogen (34 % of seasons), regardless of water availability. Conclusions: Grain yield, KW determination, and WSCS dynamics are shaped by specific hybrid-type responses to sowing date and nitrogen supply. The sowing date × nitrogen interaction is critical, as insufficient nitrogen reduces KW and grain yield, especially in early sowings. The differential remobilization of WSCS underscores distinct carbon allocation strategies in early and late sowing dates and with contrasting nitrogen availability typical of maize production systems in the central region of Argentina.